852-P: Improving the Quality of Health Care Transitions for Young Adults at an Adult Endocrinology Clinic - GILBERT, MATTHEW P.; DEVOE, STEPHEN G.; KENNEDY, AMANDA G.; OGELBY, MONICA; CONSIGLI, ALYSSA; ZIMAKAS, PAUL JAMES; REPP, ALLEN B.; ROBINSON, KEITH J. (Diabetes (New York, N.Y.), 2021)
Background: Young adults, transitioning from pediatric to adult endocrinology clinics, are at risk for adverse events. As these patients assume responsibility for their care, ensuring an effective process for health care transition (HCT) and integration into an adult clinic is imperative. Yet, there is a scarcity of data on implementing HCT best practice guidelines into adult endocrinology care using QI methodology. Objective: To improve the quality of HCTs for young adult patients (18-26 years of age) diagnosed with a variety of endocrinologic conditions by implementing Got Transition’s Six Core Elements of Health Care Transition 2.0 and utilizing the Integrating Young Adults into Adult Health Care toolkit. Methods: A team of pediatric and adult endocrinology clinicians, QI experts, and patient and family advisors (PFAs) was established to guide implementation of the Six Core Elements. Got Transition measurement tools (Current Assessment of Health Care Transition Activities-CAHCTA; Health Care Transition Process Measurement Tool-HCTPMT) were used to establish baseline scores and track progress on a quarterly basis. The team developed a “Welcome Packet” to orient and integrate young adults into adult endocrinology care. QI tools were used to identify current clinical processes and opportunities for system changes through Plan-Do-Study-Act (PDSA) cycles. Results: From October 2019 to July 2020, baseline scores improved on both the CAHCTA by 84.6% (Baseline: 13; Q1: 15; Q2: 23; Q3: 24) and the HCTPMT by 1,250.0% (Baseline: 2; Q1: 16; Q2: 25; Q3: 27). PFAs provided feedback about the Welcome Packet. PDSA Cycle 1 included a “pre-visit” during new patient visits to orient patients to adult endocrinology care using the Welcome Packet. PDSA Cycle 2 focused on piloting the Endocrine Society Patient Self-assessment. Conclusion: The implementation of HCT best practice guidelines using rigorous QI methodology can significantly improve young adults’ integration into adult health care.